INTEGRASI PENDIDIKAN LINGKUNGAN MELALUI PENDKATAN BELAJAR BERSAMA ALAM DI SEKOLAH ALAM QUR’AN BINTANG MADANI - Nadhifa Arufah Chafshah; Yuliyanti; M Eko Juliyansyah; Ali Murtadho; Bakharudin; Ikhsan Mustofa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Amid the deepening global environmental crisis, ecosystem destruction due to human activities, including climate change, pollution, and biodiversity decline, is a major challenge for both current and future generations. In the face of complex environmental problems, environmental education plays an important role in building awareness and concern for natural sustainability. One innovative approach is the integration of environmental education through the